2009
DOI: 10.1093/humupd/dmp010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soy protein and isoflavones on circulating hormone concentrations in pre- and post-menopausal women: a systematic review and meta-analysis

Abstract: BACKGROUNDHormonal effects of soy and isoflavones have been investigated in numerous trials with equivocal findings. We aimed to systematically assess the effects of soy and isoflavones on circulating estrogen and other hormones in pre- and post-menopausal women.METHODSThe Cochrane Library, MEDLINE and EMBASE (plus reviews and experts) were searched to December 2007. Inclusion of randomized or residential crossover trials of soy or isoflavones for 4 or more weeks on estrogens, SHBG, FSH, LH, progesterone and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
131
3
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 121 publications
18
131
3
3
Order By: Relevance
“…There have been reports in humans which reveal a modest suppressant effect of soy and isoflavone exposure on the hypothalamic-pituitary-gonadal axis. Although available data are highly heterogeneous, a recent metaanalysis of 47 studies concluded that consumption of soy and isoflavones in premenopausal women reduces circulating LH and FSH, and increases menstrual cycle length (Hooper et al, 2009). In contrast no statistical effects were observed on hormonal status in postmenopausal women.…”
Section: Soy Phytoestrogens and Female Fertilitymentioning
confidence: 99%
“…There have been reports in humans which reveal a modest suppressant effect of soy and isoflavone exposure on the hypothalamic-pituitary-gonadal axis. Although available data are highly heterogeneous, a recent metaanalysis of 47 studies concluded that consumption of soy and isoflavones in premenopausal women reduces circulating LH and FSH, and increases menstrual cycle length (Hooper et al, 2009). In contrast no statistical effects were observed on hormonal status in postmenopausal women.…”
Section: Soy Phytoestrogens and Female Fertilitymentioning
confidence: 99%
“…Por el contrario, cuando las ratas fueron inyectadas con estrógenos, la ingesta de ISO atenuó la acción estimuladora del estradiol sobre la expresión de la luciferasa, es decir, produjo un efecto antiestrogénico 17 . Un reciente meta-análisis de 47 protocolos sugiere que el consumo de soya o de isofl avonas, en mujeres pre o postmenopáusi-cas, no afecta los niveles circulantes de estrógenos, pero reduce signifi cativamente los niveles de FSH y LH en mujeres premenopáusicas 18 .…”
Section: Cáncer Mamariounclassified
“…This chapter does not describe the effects of soy IFs on circulating levels of estrogens and other hormones in women, and the extensive review and meta-analysis of the literature to examine these effects published by Hooper et al (2009) is recommended. Since a variety of functional foods especially formulated for women are marketed considering the putative beneficial effects of IF intake on bone health and menopausal symptoms, these subjects are briefly described.…”
Section: Bone Health and Menopausal Symptomsmentioning
confidence: 99%